Intrinsic Motivators for Job Satisfaction in the Pharmaceutical Industry of Developing Countries Using Bangladesh as a Case Study - Ahmed, Oeshwik (Thammasat Review, 2019)
Job satisfaction is one of the major influential components in the overall productivity of employees. Intrinsic factors have been linked with job satisfaction in developed countries over extrinsic factors. This research has tried to find out how intrinsic factors affect an industry in a third world country, as there have been very few studies done in this sector. The aim of the research was to discover if a developing country has the same trends for job satisfaction as a developed country or if there were other underlying factors that affected the satisfaction level among the employees in Bangladesh. The study analyzed several intrinsic components, such as: the significance of training and development, relationship between supervisor and employees and the work environment upon the overall job satisfaction of the employees. A co-relational research design has been conducted to test the hypotheses by conducting a survey of one of the leading pharmaceutical companies in Bangladesh. This research has applied both primary and secondary data analysis. Additionally, a job descriptive approach has also been used to quantify the level of work contentment. The data showed that for the chosen organization, work environment, training and development were the most important factors in determining job satisfaction; an employee’s relationship with their supervisor did not have a clear statistically significant correlation. The reason was due to the nature of the organization, being a manufacturing company, the workplace, training and development were naturally highly valued more than an employee’s relationship with their supervisor. This however falls under rationale due to the hierarchical structure of manufacturing industries where employees are subjected to repetitive controlled process with limited interaction with their supervisors. In spite of limitations in the present research, it has opened up the possibility of further investigation as to other factors of job satisfaction, especially comparative employee attitudes.